Comparative and evolutionary studies of mammalian arylsulfatase and sterylsulfatase genes and proteins encoded on the X-chromosome. (June 2017) - Holmes, Roger S.
Highlights: Amino acid sequences and secondary structures for human sterylsulfatase and arylsulfatases were examined using bioinformatic techniques. Human STS, ARSD, ARSE, ARSF and ARSH gene structures and locations demonstrated that these genes exist as an X-chromosome cluster for all mammalian genomes examined. A proposal is described for the evolutionary appearance of an STS and ARS -like gene cluster on the human X-chromosome by gene duplication and unequal cross over events. Abstract: At least 19 sulfatase genes have been reported on the human genome, including four arylsulfatase ( ARS ) genes ( ARSD ; ARSE ; ARSF ; ARSH ) and a sterylsulfatase ( STS ) gene located together on the X-chromosome. Bioinformatic analyses of mammalian genomes were undertaken using known human STS and ARS amino acid sequences to study the evolution of these genes and proteins encoded on eutherian and marsupial genomes. Several domain regions and key residues were conserved including signal peptides, active site residues, metal (Ca 2+ ) and substrate binding sequences, transmembranes and N -glycosylation sites. Phylogenetic analyses describe the relationships and potential origins of these genes during mammalian evolution. Primate ARSH enzymes lacked signal peptide sequences which may influence their biological functions. CpG117 and CpG92 were detected within the 5′ region of the human STS and ARSD genes, respectively, and miR-205 within the 3′-UTR for the human STS gene, using bioinformatic methods A proposal is described for a primordial invertebrate STS -like gene serving as an ancestor for unequal cross over events generating the gene complex on the eutherian mammalian X-chromosome.